(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Suture is a biomaterial used to approximate wound edges to facilitate the healing process. This task could be compromised as a result of wound infection. Zinc is an element that has antibacterial action and can be a member of silicate glasses. The zinc-silicate glasses can be used as a coating for surgical suture to combat wound infection. However, zinc has a negative effect on glass degradation and its antibacterial action is a pH sensitive. In this work, silicate glasseswith ZnO at 14 and 17 mole% were used as a coating for non-resorbable Mersilk suture using a slurry-dipping technique. The coating morphology was studied using SEM and itsanti-bacterial action was investigated in vitroagainstgram positive and negative bacteria at neutral and acidic conditions.The effect of the coating on tensile strength of the sutures wasstudied as well.The results revealed that the coatingwas well-adhered to the suture and had anti-bacterial action atacidic condition.The coating had no effect on the tensile strength of the surgical suture